2022
DOI: 10.1161/jaha.121.022833
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Atrial Fibrillation and Natriuretic Peptide in Predicting Heart Failure Hospitalization or Cardiovascular Death

Abstract: Background Natriuretic peptides are routinely quantified to diagnose heart failure (HF). Their concentrations are also elevated in atrial fibrillation (AF). To clarify their value in predicting future cardiovascular events, we measured natriuretic peptides in unselected patients with cardiovascular conditions and related their concentrations to AF and HF status and outcomes. Methods and Results Consecutive patients with cardiovascular con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…Moreover, clinical outcomes were not adjudicated and therefore inaccurate diagnoses as well as underreporting are possible. However, we found that the event rates were similar to those reported in a recently published contemporary study 40 . We also did not have echocardiographic assessment of the left atrial structure and function or information on medications for all patients 41,42 .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, clinical outcomes were not adjudicated and therefore inaccurate diagnoses as well as underreporting are possible. However, we found that the event rates were similar to those reported in a recently published contemporary study 40 . We also did not have echocardiographic assessment of the left atrial structure and function or information on medications for all patients 41,42 .…”
Section: Discussionsupporting
confidence: 67%
“…However, we found that the event rates were similar to those reported in a recently published contemporary study. 40 We also did not have echocardiographic assessment of the left atrial structure and function or information on medications for all patients. 41 , 42 Also, laboratory measurements were only available for a subset of patients introducing possible selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up duration ranged from 1.0 to 5.2 years. Of 16 studies included, only two studies presented data on patients with AF without HF [3,18] . The characteristics of the included studies are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine studies [2][3][4][9][10][11][12]14,16] reported MACE in AF patients, among which one study divided patient group into AF without HF and AF with HF (Figure 4). AF without HF group labeled as Brady 2022, while AF with HF labeled as Brady PF 2022 in Figure 4.…”
Section: Major Adverse Cardiovascular Eventsmentioning
confidence: 99%
“…Результаты, близкие к нашим, получены в исследовании P.F. Brady [31], в котором повышение NT-proBNP ≥1000 нг/л имеет последовательную связь с будущей госпитализацией по поводу СН или смертью от сердечно-сосудистых заболеваний (ССЗ) у пациентов с ФП с СН. NT-proBNP сохраняет прогностическую значимость у пациентов с СН и ФП [32].…”
Section: оригинальные исследованияunclassified